Comprehensive study on corrosion and discharge performance of Mg–Ca alloy with high Ca content - Yilin Xu; Xutao Zhao; Mingming Yan; Yan Zhang; Lei Shan; Yanfu Chai; Gaolei Xu; Huabao Yang; Liang Wu; Bin Jiang (Journal of Materials Research and Technology)
The corrosion and discharge performance of as-cast and extruded Mg-8.5Ca alloys have been systematically investigated as the anodes for Mg-air batteries, using electrochemical techniques and Mg-air battery tests. The extrusion deformation greatly refines the grain size, decreases the content and size of the Mg2Ca phase, and promotes the uniform distribution of the Mg2Ca phase in the matrix. The results of the Scanning Kelvin Probe Force Microscope (SKPFM) reveal that the potential difference of as-cast Mg-8.5Ca and extruded Mg-8.5Ca is approximately 60 mV and 100 mV lower than that of the α-Mg matrix, respectively. The results reveal that the Mg2Ca and α-Mg matrix in Mg-8.5Ca alloys act as micro-anode and micro-cathode, respectively. The superior potential difference renders extruded Mg-8.5Ca to have strong micro-galvanic corrosion, which enhances the electrochemical and discharge performance. For extruded Mg-8.5Ca alloy, the corrosion performance of the alloy is effectively enhanced, and hydrogen evolution during discharge is largely inhibited. The extruded Mg-8.5Ca anode exhibits excellent comprehensive discharge performance, with the highest anode utilization and specific capacity of 44.6 %, and 914.1 mAh⋅g−1 at 10 mA cm−2, respectively. The discharge voltage and anode utilization of the as-cast Mg-8.5Ca decrease severely, attributed to the excessive Mg2Ca phase and coarse and uneven grain size accelerating the self-corrosion and causing the severe chunk effect.